Pengaruh Pemberian Aromaterapi Lemon terhadap Penurunan Dismenore pada Remaja Putri - Antri Ariani; Yanyan Mulyani; Rosifa Rosifa (Jurnal Kebidanan Harapan Ibu Pekalongan, 2023)
Dysmenorrhea is also known as menstrual cramps or menstrual pain. In Indonesia, there is a prevalence of dysmenorrhea of 64,5% in adolescents aged 17-24 years. Which affect fatigue, pain in the area below the waist, feelings of anxienty and tension, headaches, confusion, nausea and vomiting, diarrhea, stomach cramps and abdominal pain and activity disturbances. The most common symptons felt by midwifery students who experienced dysmenorrhea were low back pain and lower abdominal pain. In English, dysmenorrhea is often referred to as a "painful period" or painful menstruation, menstruation is usually with cramping and pain centered in the lower abdomen. One of the treatments to reduce dysmenorrhea with non- pharmacological therapy is by giving lemon aromatherapy. Limeone is one of the ingredients in lemon aromatherapy oil that can inhibit the prostaglandin working system so that it can reduce pain. The purpose of this study was to determine the effect of lemon aromatherapy in reducing dysmenorrhea in teenage girl. This study uses a pre-experimental method with a one-group-pre-test-post-test- design. The sample consisted of 35 respondents with the sampling method using a purposive sampling approach. The results using the dependent T-test (paired sample T-test) obtained a p-value of 0.000 (p<0.05). There is an effect of giving lemon aromatherapy to decrease dysmenorrhea in Midwifery students, Faculty of Health Sciences at Bhakti Kencana University. So it is hoped that lemon aromatherapy can be used as a therapy to reduce dysmenorrhea which is a complementary therapy